Review of Simon Jeffes: Music from the Penguin Cafe, Roger Dean’s Lysis: Lysis Live, David Rosenboom & J.B. Floyd: Suitable for Framing, The Sounds of Sound Sculpture, and David Rosenboom: Brainwave Music - Roberts, David (Contact: A Journal for Contemporary Music (1971-1990), 1977)